2011
DOI: 10.1063/1.3560386
|View full text |Cite
|
Sign up to set email alerts
|

Experimental control of vortex breakdown by density effects

Abstract: International audienceThe vortex breakdown inside a cylinder with a rotating top lid is controlled experimentally by injecting at the bottom a fluid with a small density difference. The density difference is obtained by mixing a heavy dye or alcohol with water in order to create a jet denser or lighter than water. The injection of a heavy fluid creates a buoyancy force downward, which counteracts the meridional recirculation in the cylinder and thus enhances the formation of a vortex breakdown bubble. The stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…One review of the progress made in breakdown control is Mitchell and Delery, 12 and research into control methods is continuing. [13][14][15][16][17] Despite the significant control demonstrated however, these methods appear not to have contributed to breakdown control in practice. The current solution for the F/A-18, for instance, is the placement of a vortex generator on the surface of the leading-edge extension to divert the vortex outboard of the vertical stabilizers, where breakdown when it does occur can do less harm.…”
Section: Introductionmentioning
confidence: 64%
“…One review of the progress made in breakdown control is Mitchell and Delery, 12 and research into control methods is continuing. [13][14][15][16][17] Despite the significant control demonstrated however, these methods appear not to have contributed to breakdown control in practice. The current solution for the F/A-18, for instance, is the placement of a vortex generator on the surface of the leading-edge extension to divert the vortex outboard of the vertical stabilizers, where breakdown when it does occur can do less harm.…”
Section: Introductionmentioning
confidence: 64%
“…This method is considered to be accurate and relatively fast (about 0.5 min). The absolute accuracy of the instrument is said to be 0.001 g/cm 3 , but apparently, it is higher (Ismadi, Meunier, Fouras, & Hourigan, ). After many (20) measurements, we conclude that the deviation is merely 0.0001 g/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Second, the successful formation of vortex breakdowns was described when a fluid with smaller density was injected into the water inside a cylinder that had a rotating top lid. 33 These authors observed that a small density difference of 0.02% halved the critical Reynolds number for the appearance of vortex breakdown, a fact that was not averted either by using a lighter fluid. For density differences larger than 0.03%, they also found that the lighter fluid pierced through the bubble, which resulted in a new structure of vortex breakdown.…”
Section: Introductionmentioning
confidence: 95%